2017
DOI: 10.1016/j.stem.2016.12.002
|View full text |Cite|
|
Sign up to set email alerts
|

RNA Helicase DDX5 Inhibits Reprogramming to Pluripotency by miRNA-Based Repression of RYBP and its PRC1-Dependent and -Independent Functions

Abstract: RNA-binding proteins (RBPs), in addition to their functions in cellular homeostasis, play important roles in lineage specification and maintaining cellular identity. Despite their diverse and essential functions, which touch on nearly all aspects of RNA metabolism, the roles of RBPs in somatic cell reprogramming are poorly understood. Here we show that the DEAD-box RBP DDX5 inhibits reprogramming by repressing the expression and function of the non-canonical polycomb complex 1 (PRC1) subunit RYBP. Disrupting D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 46 publications
4
64
0
1
Order By: Relevance
“…DDX5 plays an important role in miRNA processing. For example, DDX5 inhibits reprogramming to pluripotency through its role in producing mature miR‐125b . Further study is required to determine whether DDX5 regulation of autophagy involves miRNA processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DDX5 plays an important role in miRNA processing. For example, DDX5 inhibits reprogramming to pluripotency through its role in producing mature miR‐125b . Further study is required to determine whether DDX5 regulation of autophagy involves miRNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…(25) Recently, DDX5 has been reported to act as a reprogramming roadblock, regulating pluripotency gene expression through its role in miRNA processing. (26) HBV-associated HCC patients exhibit reduced DDX5 expression (25) ; other studies have shown HCCs with reduced autophagy and accumulation of p62 (3,27) to associate with poor prognosis after tumor resection. (1) These findings suggest a link between DDX5 downregulation and autophagy.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…This study indicated the existence of a RYBP‐miR‐29 feedback loop that may play a key role in skeletal myogenesis . During reprogramming, loss of DDX5 acted as a promoter of somatic cell reprogramming by repressing miR‐125b expression, which in turn, resulted in the RYBP up‐regulation . Intriguingly, enhanced RYBP not only suppressed lineage‐specific genes by increasing monoubiquitination of histone H2A at lysine‐119 (H2AK119ub1) levels through PRC1, but also activated pluripotency‐promoting genes by facilitating the recruitment of OCT4 to the Kdm2b promoter .…”
Section: The Roles Of Rybp In Developmentmentioning
confidence: 92%
“…During reprogramming, loss of DDX5 acted as a promoter of somatic cell reprogramming by repressing miR-125b expression, which in turn, resulted in the RYBP up-regulation [15]. Intriguingly, enhanced RYBP not only suppressed lineage-specific genes by increasing monoubiquitination of histone H2A at lysine-119 (H2AK119ub1) levels through PRC1, but also activated pluripotency-promoting genes by facilitating the recruitment of OCT4 to the Kdm2b promoter [15]. Thus, this study suggested that DDX5 controlled reprogramming through the PRC1-dependent and PRC1-independent functions of RYBP.…”
Section: The Roles Of Rybp In Developmentmentioning
confidence: 99%